The feasibility, acceptability, and usability of telehealth visits - Sinha Gregory, Naina; Shukla, Alpana P.; Noel, Jahi J.; Alonso, Laura C.; Moxley, Jerad; Crawford, Andrew J.; Martin, Peter; Kumar, Sonal; Leonard, John P.; Czaja, Sara J. (Frontiers in Medicine, 2023)
Background Telemedicine is now common practice for many fields of medicine, but questions remain as to whether telemedicine will continue as an important patient care modality once COVID-19 becomes endemic. We explored provider and patients’ perspectives on telemedicine implementation. Methods Physicians from three specialties within the Department of Medicine of a single institution were electronically surveyed regarding their perceptions of satisfaction, benefits, and challenges of video visits, as well as the quality of interactions with patients. Patients were surveyed via telephone by the Survey Research Group at Cornell about participation in video visits, challenges encountered, perceived benefits, preferences for care, and overall satisfaction. Results Providers reported an overwhelmingly positive experience with video visits, with the vast majority agreeing that they were comfortable with the modality (98%) and that it was easy to interact with patients (92%). Most providers (72%) wanted to have more telemedicine encounters in the future. Key factors interfering with successful telemedicine encounters were technical challenges and insufficient technical support. Overall, patients also perceived video visits very positively regarding ease of communication and care received and had few privacy concerns. Some (10%–15%) patients expressed interest in receiving more technical support and training. There was a gradient of satisfaction with telemedicine across specialties with patients receiving weight management reporting more favorable responses while patients with lymphoma expressed more mixed responses. Conclusion Both providers and patients found telemedicine to be an acceptable and useful modality to provide or receive medical care. The principal barrier to successful encounters was technical challenges.